PREPARATION OF SILVER AND COPPER NANOPARTICLES IN PRESENCE OF ASCORBIC ACID AND INVESTIGATION OF THEIR ANTIBACTERIAL ACTIVITY - Laban, Bojana; Košanin, Milena; Isić, Goran; Ralević, Uroš; Marković, Mirjana; Jokić, Anja; Vasić, Vesna (Bulletin of Natural Sciences Research, 2017)
In this study, we present a synthesis of silver and copper nanoparticles (NPs) using ascorbic acid as stabilizing and sodium borohydride as reducing agents, respectively. Four colloidal dispersions were obtained, two of them additionally stabilized by gelatin. They were characterized by UV-Vis, AFM, DLS and zeta potential measurements. The size of both silver and copper NPs, determined by AFM measurements, was 10 nm before, and 15 nm after stabilization with gelatin. Antibacterial activity of synthesized NPs was tested using series of gram positive and gram negative bacteria. It was found that Ag and Cu NPs showed antibacterial activity in all cases.